An analytical model for inelastic cyclic response of eccentrically braced frame with vertical shear link (V-EBF). (December 2016) - Bouwkamp, Jack; Vetr, Mohamad Ghasem; Ghamari, Ali
Highlights: We have continued the past researches on strain hardening of EBFs. The tested models have been classified in three parts. A new analytical model with high accurate results have proposed. Our study is a new investigation on V-EBF. Abstract: Eccentrically Braced Frames (EBFs) have a capability of energy dissipation relying on horizontal link beams in main frame. Use of vertical link (V-EBF) enhances system performance; main frame damaged, easy replaces after earthquake, and it can be rehabilitated minor changes of existing structure. This paper describes experimental and analytical study of the V-EBF system. Experimental results showed that ultimate shear strength of vertical link is more than two times of yielding strength. In analytical model, Kinematic-Isotropic strain hardening for shear, and only Kinematic for moment, showed accurate results with an upper bound for yielding surface to the vertical link.